2019
DOI: 10.2337/dc19-0120
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Late-Life Diabetes Status and Hyperglycemia With Incident Mild Cognitive Impairment and Dementia: The ARIC Study

Abstract: We sought to examine associations in older adults among diabetes, glycemic control, diabetes duration, and biomarkers of hyperglycemia with incident mild cognitive impairment (MCI) and incident dementia. RESEARCH DESIGN AND METHODS We conducted a prospective analysis of 5,099 participants from the Atherosclerosis Risk in Communities (ARIC) Study who attended the fifth (2011-2013) exam. Cognitive status was assessed during follow-up via telephone calls, death certificate codes, surveillance, and a follow-up exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 43 publications
6
103
3
1
Order By: Relevance
“…This study shows that 83.9% type 2 diabetic elderly patients with MCI have poor glycaemic control. This observation is novel in the Polish population, and the result is consistent with other studies which presented high associations between poor glycaemic control and cognitive impairment in diabetics worldwide [21,22,23]. Data from cross-sectional studies agree that a chronic hyperglycaemic state causes cognitive function deficit.…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that 83.9% type 2 diabetic elderly patients with MCI have poor glycaemic control. This observation is novel in the Polish population, and the result is consistent with other studies which presented high associations between poor glycaemic control and cognitive impairment in diabetics worldwide [21,22,23]. Data from cross-sectional studies agree that a chronic hyperglycaemic state causes cognitive function deficit.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that poor glycemic control is an important factor related to cognitive decline. But the studies using high HbA1c levels to measure this have shown some conflicting results [ 4 , 14 17 ]. Therefore, at the moment, the association between HbA1c and cognitive decline in patients with T2DM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…An increase of HbA 1c by 1mmol/mol was associated with a significantly increased rate of decline in cognitive scores and executive function . More recent data from the ARIC study (Atherosclerosis Risk in Communities) found an increased incidence of mild cognitive impairment and dementia in patients with longer diabetes duration (over five years) and poor glycaemic control, further adding support to the hyperglycaemia theory …”
Section: Hyperglycaemiamentioning
confidence: 85%